Exploring the Impact of Spousal Compatibility (Kafa’ah) on Marital Harmony: A Comprehensive Literature Review - Evanurfitriani (Formad English Foundation NTB Jakarta, 2025)
This study is motivated by the limited research on spousal compatibility (kafa’ah), despite its significant impact on marital harmony and family stability. While kafa’ah is a foundational concept in Islamic marital jurisprudence, contemporary scholarship has not fully integrated classical perspectives with modern empirical findings. Therefore, this study aims to systematically explore the dimensions of kafa’ah and analyze how these dimensions influence marital harmony through a comprehensive literature review. The research adopts a qualitative design, synthesizing findings from peer-reviewed journal articles, classical Islamic texts, and contemporary family studies selected through purposive sampling. Data were collected through document analysis and examined using thematic analysis to identify recurring patterns related to compatibility and marital outcomes. The findings reveal three major dimensions of kafa’ah: religious–spiritual, emotional–communicative, and socioeconomic–cultural compatibility. Religious compatibility consistently emerges as the most influential factor shaping marital stability, while emotional and communication alignment strengthens conflict management and relational intimacy. Socioeconomic and cultural compatibility further supports cooperation in daily marital functioning. These results align with both classical Islamic scholarship and contemporary relationship psychology, demonstrating coherence between traditional jurisprudence and modern scientific understanding. The study concludes that kafa’ah plays a critical multidimensional role in enhancing marital satisfaction, reducing conflict, and strengthening emotional and spiritual bonds. The implications include theoretical contributions to the integration of Islamic family law and family psychology, as well as practical recommendations for marriage counselors, religious leaders, and policymakers to emphasize multidimensional compatibility in premarital guidance. Future research is encouraged to examine kafa’ah using empirical or longitudinal approaches to deepen understanding within diverse cultural contexts.